2016
DOI: 10.1063/1.4963285
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of UV-induced charge accumulation in inverted-type polymer solar cells with a TiOx layer: Microscopic elucidation of the light-soaking phenomenon

Abstract: The mechanism of light-soaking phenomenon in inverted-type organic solar cells (IOSCs) with a structure of indium-tin-oxide/TiOx/P3HT:PCBM/Au was studied by electron spin resonance (ESR) spectroscopy. Charge accumulation in the cell during UV-light irradiation was observed using ESR, which was clearly correlated with the light-soaking phenomenon. The origin of the charge accumulation is clarified as holes that are deeply trapped at p-type P3HT polymer-chain ends with bromine after hole transfer from the band e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(81 citation statements)
references
References 35 publications
6
75
0
Order By: Relevance
“…To attain a high signal‐to‐noise (SN) ratio of the ESR signal by increasing the active area of the device, we utilized a rectangular device structure (3 × 20 mm 2 ) in an ESR sample tube with an inner diameter of 3.5 mm and a length of 270 mm . Figure shows the device structure of indium‐tin‐oxide (ITO) (150 nm)/NPB (60 nm)/Alq 3 (60 nm)/LiF (0.5 nm)/Al (100 nm) used in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To attain a high signal‐to‐noise (SN) ratio of the ESR signal by increasing the active area of the device, we utilized a rectangular device structure (3 × 20 mm 2 ) in an ESR sample tube with an inner diameter of 3.5 mm and a length of 270 mm . Figure shows the device structure of indium‐tin‐oxide (ITO) (150 nm)/NPB (60 nm)/Alq 3 (60 nm)/LiF (0.5 nm)/Al (100 nm) used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, halogens are generally used for the NPB synthesis and may possibly remain in NPB molecules. Actually, it has been reported that the g factor of the ESR signal of a conducting polymer poly(3‐hexylthiophene) (P3HT) becomes larger by residual bromines at polymer‐chain ends of P3HT . To examine the possibility of residual halogens, we performed the quantitative analysis of the content of halogens in the NPB material used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Also, an intrinsic reversible deterioration mechanism during device operation has been discussed for a polymer solar cell with blend films of regioregular poly(3-hexylthiophene) (P3HT) and [6,6]-phenyl C 61 -butyric acid methyl ester (PCBM) [16,17]. The deterioration has been ascribed to an accumulation of photogenerated charges during device operation [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…This ESR method has clarified the charge formation in pentacene/C 60 layered thin-film solar cells during device fabrication [25,26]. For the P3HT:PCBM polymer solar cells, the molecules with the charge accumulation during device operation have been identified as P3HT using the ESR method [18][19][20]. However, the detailed charge accumulation states in P3HT have not yet been completely clarified.…”
Section: Introductionmentioning
confidence: 99%
“…We had also investigated the mechanism of the both lightsoaking effect observed in the polymer solar cells using both ac impedance spectroscopic (IS) and electron spin resonance (ESR) measurements. 17,18,20 We have found that these light soaking effects are caused by favorable charge accumulations for suppressing the recombination and disappearing the charge-injection barrier between the electron collection electrode and the organic active layer. The expression of the effects needs to excite the electron collection layer such as n-type semi-conductive metal oxide by UV-light irradiation.…”
Section: Introductionmentioning
confidence: 99%